Description of the Immature and Adult Stages of Ectatomma vizottoi (Formicidae: Ectatomminae) - Vieira, Alexsandro S.; Antonialli-Junior, William F.; Fernandes, Wedson D.; Tofolo, Viviane C. [UNESP]; Giannotti, Edilberto [UNESP] (California State University, 2009)
We estimated the number of larval instars of the ant Ectatomma vizottoi (Ectatomminae), by measuring the maximum width of the head capsules of 208 larvae and the morphology of the immature stages (eggs, larvae and pupae) and adults. There are three larval instars during the post-embryonic development. The reproductive eggs are dark brown. Hairs are present beginning with the first instar, are uniformly distributed over the larval body, and do not vary in length in the three instars. Pupae are protected by a light-brown silk cocoon. Adults of the worker and queen castes can be differentiated by size.
Keywords: ants; cephalic capsule; Dyar's rule; larval instars